Synthesis, solution, and structural characterization of tetrahydrofuranyl-2,2-bisphosphonic acid disodium salt - Maltezou, Elena; Stylianou, Marios; Roy, Sudeshna; Keramidas, Anastasios D.; Drouza, Chryssoula (My University, 2010)
Bisphosphonates are biologically relevant therapeutics for bone disorders and cancer. Reaction of γ-chlorobutyric acid, phosphorus acid, and phosphorus trichloride without the use of solvent gave the tetrahydrofuranyl-2, 2-bisphosphonate sodium salt (Na2H2L). The Na 2H2L was isolated, characterized in solution by 1H, 13C, and 31P NMR spectroscopy and in solid state by single X-Ray crystallography. The crystal structure showed that the Na2H2L forms in the crystal infinite two-dimensional sheets stacked one parallel to the other. A comparison of the chelating properties of H2L2- with similar hydroxyl bisphosphonate ligands shows that the strength of the NaO(furanyl/hydroxyl) bond is directly related to the total charge of the ligand anion
Keywords: Diphosphonates; Diphosphates; Pyrophosphate synthase